Sumberdaya Dalam Penanganan Anak Korban Kekerasan Seksual Pada Dinas Pemberdayaan Perempuan dan Perlindungan Anak Kabupaten Kolaka Sulawesi Tenggara - Hendik, Hendrik; Jamaluddin, Indar Ismail; Septiana, Anis Ribcalia (Morality: Jurnal Ilmu Hukum; Vol 10 No 1 (2024): Morality : Jurnal Ilmu HukumDO - 10.52947/morality.v10i1.421, 2024)
Kolaka Regency Regional Regulation Number 3 of 2016 concerning the Implementation of Child Protection explains that handling child victims of sexual violence includes identifying and receiving complaints; rescue; placement in temporary shelter; rehabilitation; health, social, psychological, and legal assistance recovery services; as well as post-rehabilitation service support (article 24). This research aims to analyze aspects of resources for handling child victims of sexual violence at the Women's Empowerment and Child Protection Service, Kolaka Regency, Southeast Sulawesi. This type of qualitative research uses purportive selection of informants, consisting of policy formulators (representatives of the Regent and Kolaka DPRD) and policy implementers, namely the Head of the Kolaka Women's Empowerment and Child Protection Service (DP3A) and the Head of the Technical Implementation Unit of the Women and Child Protection Service (UPTD). Observations and secondary data, including government websites, online media reports, and scientific articles, complete the data collection. The research results show that the resource aspect of handling child victims of sexual violence in Kolaka has been implemented with the following conditions: First, with 22 employees, DP3A Kolaka has not responded optimally to complaints of violence against children. Second, DP3A Kolaka has a psychologist, even though he doesn't have a competency certificate, as well as 12 midwives. Skills are learned autodidactically. Third, DP3A Kolaka implemented the delivery of information by telephone and collaborated with the Kolaka Police, religious courts, non-government organizations, and mass media. Fourth, authority for the program refers to Regional Regulation Number 3 of 2016 concerning Implementation of Child Protection and Kolaka Regent Regulation Number 35 of 2020 concerning Child Friendly Districts. In 2021–2022, it will be implemented by the Task Force Team. Fifth, budget support, facilities, and infrastructure come from the APBN and APBD. Budget limitations are not a problem for the head of DP3A Kolaka.